SEX IDENTIFICATION OF HUMAN REMAINS FROM AN IRISH MEDIEVAL POPULATION USING BIOMOLECULAR METHODS - Tierney, Sheila; Bird, Jeremy (European Scientific Journal, ESJ, 2014)
The excavation of a medieval cemetery in County Donegal has allowed the recovery of one of the largest assemblages of human remains from a burial ground in Ireland to date. In order to enhance the interpretation of the assemblage and give a more complete picture of the Ballyhanna community as a whole, a sample of the juvenile population from Ballyhanna were sexed using DNA based techniques. Sex identification of human remains is generally assigned using skeletal morphology or on some occasions using associated grave goods. When an assemblage contains immature or fragmentary material, an alternative and reliable means of sexing these individuals is required. In this research project the reproducibility of two PCR based sexing methods were evaluated on 38 adults of known sex to determine the accuracy of the methodology for sexing individuals from the Ballyhanna assemblage. Using real time PCR and STR profiling, a reliable sexing system was developed for adult remains which was validated against osteoarchaeological sexing. The reproducibility of the results from the amplified samples meant that the methodologies were valid and could be used to sex juveniles from the assemblage. The molecular sexing results from nineteen juveniles sampled determined that four of the juvenile individuals were males, 10 were probable males, one was a probable female and four were inconclusive. The results from this study, although they may not be fully representative of the entire juvenile population excavated from this cemetery, indicate higher levels of juvenile male mortality than female.